Spiritual Piety and Social Pity: Study of Sufism Thought Bawa Muhaiyadden as a Contemporary Sufi - Mursalat Mursalat (Program studi Keagamaan Islam, 2023)
The Bawa Muhaiyaddeen Fellowship was founded in Philadelphia in the 1970s with a focus on universal spirituality. Bawa Muhaiyaddeen, a prominent figure, played a key role in connecting Sufi heritage to the United States. Bawa Muhaiyaddeen's teachings have become an important part of Sufism's history in America. He successfully united various perspectives on the relationship between Sufism and Islam, Sufis and Muslims, Sufis and Non-Muslims, as well as Muslims and non-Sufis. This research used a qualitative approach with the ethnography method and analyzed media using the AMS (Siber Media Analysis) technique. The findings reveal that Sufis prioritize the afterlife and strive to control their impulses to avoid harming themselves and others. Bawa Muhaiyaddeen emphasized that Sufis should also strive to be more competitive than those who focus solely on fulfilling their desires and greed.